Methods for Detection of Bacterial Endotoxin in Critical Care Medicine - M. N. Kopitsyna; A. S. Morozov; I. V. Bessonov; V. M. Pisarev (Общая реаниматология, 2018)
Dedicated to reviewing the methods for detecting bacterial endotoxin in aqueous solutions and biological fluids, this review is focused on determining the content of endotoxin as a clinically relevant biomarker of sepsis caused by Gram-negative bacteria. The advantages and disadvantages of each method are described, and the characteristics of test systems currently used in clinical practice are listed and compared.